2009
DOI: 10.1080/08961530802153185
|View full text |Cite
|
Sign up to set email alerts
|

How Young Adult Consumers Evaluate Diffusion Brands: Effects of Brand Loyalty and Status Consumption

Abstract: This paper evaluates how brand loyalty may affect young status consumers' evaluation of diffusion brands for high/low involvement fashion products. In particular, the positioning strategy of the type of diffusion brand names is investigated in this study. Data were gathered through an experimental research design from 739 young status consumers studying in a large university. The findings revealed that sub-brands and nested brands with different country of origins have similar product quality and brand image e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 101 publications
1
42
0
Order By: Relevance
“…The evaluation of brands as symbols of prestige and success did not confirm results of Phau andCheong (2009) andO'Cass andSiahtiri (2013). On the other hand, discounts and sales offers are positively perceived by Generation Y as well as Ballard et al, (2013) claims.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The evaluation of brands as symbols of prestige and success did not confirm results of Phau andCheong (2009) andO'Cass andSiahtiri (2013). On the other hand, discounts and sales offers are positively perceived by Generation Y as well as Ballard et al, (2013) claims.…”
Section: Discussionmentioning
confidence: 66%
“…They use them not only because of their high quality, but also due to social standing (Phau & Cheong, 2009;O'Cass & Siahtiri, 2013). According to Eastman and Liu (2012) Generation Y has the highest level of motivation to consume for status compared to Generation X and Baby boomers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The concept of status consumption can be beneficial in understanding consumer preferences and brand loyalty because status-seeking consumers show higher commitment than other consumers toward a brand with a unique image and values for demonstrating social status (Eastman & Eastman, 2011;O'Cass & Frost, 2002;Phau & Cheong, 2009). Recent empirical research has shown that travelers are interested in luxurious cruise travel experiences because luxury consumers believe that luxurious cruise brand reflects their social image (Hwang & Han, 2014).…”
Section: The Moderating Role Of Status Consumptionmentioning
confidence: 99%
“…They do this not only because of their high quality, but also because of their social status [44,45]. According to Eastman and Liu in [46].…”
Section: Generation Ymentioning
confidence: 99%